Dampak Cybercrime: Analisis Tingkat Kepercayaan Masyarakat Terhadap Perbankan Syariah - MH Ainulyaqin; Adrianna SR; Listian I. Achmad; Yudianto Achmad; Devi Qolifaturrodiyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to explain the level of customer trust in Islamic banking and also explain the results of the analysis of the level of trust of Islamic banking customers affected by cybercrime. Cybercrime attacks against the Islamic banking sector, one of which is cybercrime that has occurred at Bank Syariah Indonesia (BSI), was attacked by a dangerous ransomware virus, the impact of a cyber ransomware attack carried out by a group of hackers calling themselves the LockBit Ransomware Group which is one type of malware or malicious software that locks the victim's data or device. The research method used is qualitative, the data collection technique uses a questionnaire and then analyzes the results of the questionnaire, In research on the level of trust in Islamic banking, it was found that the majority of respondents showed high trust, this trust is based on factors such as transparency in operations and the need for sharia principles which are the main basis for customers. However, this study also found that the minority of respondents' trust decreased due to the disruption of the Bank Syariah Indonesia (BSI) service system, causing customers to worry about the Islamic banking security system used.